There is no subject. Long live the citizen! (El Taco en la Brea, 2019)
In contemporary thought, the subject, understood as a modern synthesis of the transcendental and the phenomenal, has become a limit, rather than a foundation. Civil war or stasis is nowadays the very condition of the political and that, as such, the viability of the subject depends on its participation in the agony of democracy. Fifty years after 1968, an exhibition (Protest! Resistance in the poster) provides not only an atlas of visual memory as well as an appeal to the need for resistance, but it also shows the place of the Latin-American subject from an European point of view.
Keywords: subject; democracy; political struggle; resistance; stasis